Functional expression of the chemokine receptor XCR1 on oral epithelial cells - Khurram, Syed A; Whawell, Simon A; Bingle, Lynne; Murdoch, Craig; McCabe, Brenka M; Farthing, Paula M (The Journal of pathology, 2010)
Chemokines are chemoattractant cytokines which act on specific receptors and play an important role in leukocyte migration as well as physiological and pathological processes. We investigated the role of the chemokine receptor XCR1 and its ligand lymphotactin (Lptn/XCL1) in the regulation of oral epithelial cell behaviour. In vitro XCR1 mRNA and cell surface protein expression was detected in normal oral keratinocytes and oral squamous cell carcinoma cell lines. Lymphotactin mediated intracellular activation of the ERK1/2 signalling pathway and stimulated migration, invasion, and proliferation of all cells through XCR1. Oral cancer cells showed a greater response to lymphotactin than normal keratinocytes and a direct relationship between receptor expression and migration, invasion, and proliferation was observed. Exposure of normal keratinocytes to lymphotactin resulted in increased adhesion to fibronectin but not collagen and stimulated MMP-2 and MMP-9 but not MMP-7 release, whereas exposure of cancer cells resulted in increased adhesion to both collagen and fibronectin and stimulated production of MMP-2, MMP-9, and MMP-7. We observed XCR1 but not lymphotactin to be expressed by epithelial cells in normal oral mucosa in vivo, whilst both were expressed and up-regulated in inflammatory oral disease and oral cancer including primary and metastatic disease. Lymphotactin mRNA and constitutive intracellular protein were detected in normal keratinocytes and oral cancer cell lines in vitro. These findings show that XCR1 and its ligand, lymphotactin, are expressed by oral epithelial cells and suggest that they play a role in regulating the behaviour of these cells. Copyright © 2010 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.